Management of Antibiotic-Resistant Pathogens in Clinical and Chronic Mastitis using Pashu Ayurveda (Ethnoveterinary) Formulations: A Field-Based Interventional Study - Kumar, S. K.; Magare, Vijay; Gore, Subhash; Godbole, Yogesh; Darshan, Raj N (European Journal of Applied Sciences, 2026)
Background: Bovine mastitis remains one of the most prevalent diseases affecting dairy animals worldwide and represents a major cause of economic loss and antimicrobial resistance (AMR). Indiscriminate and prolonged antibiotic usage in mastitis management has resulted in therapeutic failures, drug residues in milk, and the emergence of multidrug-resistant pathogens. Objective: The present study aimed to identify antibiotic-resistant mastitis pathogens and to evaluate the clinical and microbiological efficacy of a standardized Pashu Ayurveda (ethnoveterinary) formulation in the management of clinical and chronic mastitis. Methods: A field-based interventional study was conducted on 100 dairy animals diagnosed with clinical or chronic mastitis between January 2020 and December 2023. Milk samples were subjected to bacteriological culture, antibiotic sensitivity testing, somatic cell count (SCC) analysis, and pH estimation. A standardized ethnoveterinary formulation was administered topically for 10 consecutive days, along with internal herbal supplementation. Clinical and laboratory parameters were recorded before and after intervention. Statistical analysis was performed using paired proportion tests. Results: Significant improvement was observed in clinical parameters, including abnormal milk colour, udder swelling, flakes in milk, pain during milking, and udder fibrosis (P ≤ 0.01). Normal milk pH increased from 31% to 48% (P = 0.027). High and very high SCC categories showed a marked reduction (P ≤ 0.001). Antibiotic resistance declined from 100% at baseline to 2% post-treatment, with 92% of isolates regaining antibiotic sensitivity. The overall recovery rate was 79.38%. Conclusion: The Pashu Ayurveda (ethnoveterinary) formulation demonstrated significant clinical and microbiological efficacy in managing antibiotic-resistant mastitis, improving milk quality, reducing inflammatory burden, and restoring antibiotic responsiveness. This approach offers a sustainable, residue-free alternative aligned with antimicrobial stewardship and the One Health framework.